Development of water quality modelling using InfoWork river simulation in Malacca river, Malaysia and contribution towards total maximum daily load approach - Che Osmi, Siti Aisyah; Wan Ishak, Wan Faizal; Azman, Mohammad Adam; Ismail, Abdullah Siddiqi; Abu Samah, Nurlin (2018)
Nowadays, development and urbanization have increase the pollutant loads in the river. As one of important water resource, river has been threatened by the increasing of pollutant loads in the river body. The water quality modelling is an important tool to simulate water quality analysis and river management by addition of pollutant loads. The needs of effective watershed management are crucial to ensure the river is well managing and regulated. In Malaysia, Malacca River has become one of the most popular place for tourism activities. Present work has developed water quality modelling by using InfoWork River Simulation version 10.5, to simulate the water quality condition by doing pollution reduction analysis. The modelling framework is developed to simulate the load reduction for Chemical Oxygen Demand (COD) as the pollutant controlled at the selected area. The simulation shows that, based on four scenarios created, Scenario 3 are selected as the best condition to achieved Class II water quality standard. As a conclusion, the development of water quality modelling by using InfoWork (RS) can improve the water quality condition at Malacca River by using pollution loading reduction analysis and suggested for future watershed management such as Total Maximum Daily Load (TMDL) implementation plan.